Disturbance-observer-based LQR control of singularly perturbed systems via recursive decoupling methods. Issue 4 (12th March 2019) - Xu, Jing; Niu, Yugang
ABSTRACT: This paper addresses the disturbance-observer-based linear quadratic regulation (LQR) problem of singularly perturbed systems subject to harmonic disturbances. To reduce the computational burden and facilitate the on-board implementation, a recursive matrix decoupling method is proposed to decompose the stiff singularly perturbed model into the block-diagonal form. Then, a robust LQR controller is designed based on the equivalent decoupled system, which consists of a state feedback controller for performance optimisation and a robust controller for disturbance compensation. Moreover, the designed controller is integrated with a finite frequency disturbance observer to attenuate the effect of harmonic disturbances. Finally, a simulation example on a DC motor system is provided to verify the effectiveness of the proposed design method.